2020
DOI: 10.15835/nbha48111626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the interaction between shade and drought on physiological characteristics in Calamus viminalis seedlings

Abstract: Recently, the endangerment of wild rattan population draws attention on the conservation and sustainable utilization of rattan resources. Rattan growing usually faces the light and water stress. Therefore, we aim to explore the combined effects of shade and drought on seedling growth, thus providing a theoretical ground for the conservation and artificial cultivation of the rattan. The combined effects of shade and drought on physiological and biochemical traits were studied in two-years-old Calamus viminalis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This result is significant, meaning that shading stress does not affect plants as proline is an important osmolyte that plays a vital role in regulating plant cell osmotic pressure and alleviating damage caused by stress conditions (Haffani et al, 2014; Mahajan & Tuteja, 2005). This result is also consistent with the results of Chen et al (2020) who investigated the effects of the interaction between shade and drought on physiological traits of Calamus viminalis seedlings (a climbing plant of the Palmae family). Regarding proline content, their results showed that it was lower under full light than in mild and moderate shading but increased significantly with deep shading.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is significant, meaning that shading stress does not affect plants as proline is an important osmolyte that plays a vital role in regulating plant cell osmotic pressure and alleviating damage caused by stress conditions (Haffani et al, 2014; Mahajan & Tuteja, 2005). This result is also consistent with the results of Chen et al (2020) who investigated the effects of the interaction between shade and drought on physiological traits of Calamus viminalis seedlings (a climbing plant of the Palmae family). Regarding proline content, their results showed that it was lower under full light than in mild and moderate shading but increased significantly with deep shading.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding proline content, their results showed that it was lower under full light than in mild and moderate shading but increased significantly with deep shading. This suggests the damage caused by full light and deep shading triggers a large accumulation of proline in the plant (Arora & Saradhi, 2002; Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies found that low light intensity can impact disease resistance in plants, and many works proved that plants reduced stress tolerance under light deficiency [50][51][52][53][54][55][56]. Moreover, our previous study also found that light deficiency impacted stress tolerance in M. sinostellata [64].…”
Section: Discussionmentioning
confidence: 87%
“…Given that low light intensity can impact stress tolerance in various plants, such as Calamus viminalis, Anoectochilus roxburghii, and Leymus chinensis [50][51][52], and light deficiency also weakened the resistance of M. sinostellata [53], stress response TFs were identified and analyzed in a genome wide range. TIFY and mitochondrial transcription termination factors (mTERFs) are related to stress response and have important roles in stress tolerance in plants [72,73].…”
Section: Light Deficiency Affected Stress-related Transcription Factors In M Sinostellatamentioning
confidence: 99%
See 1 more Smart Citation